Rancang Bangun Sistem Informasi Akademik Berbasis Web: Studi Kasus: SD Negeri 18 Tanah Abang - Putri Marlina Ariansyah; Khana Wijaya (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
SD Negeri 18 Tanah Abang is one of the elementary schools located in Tanjung Dalam Village. In line with the rapid development of technology, there are demands on educational institutions or others to provide fast, precise, and accurate information. In processing the data, SD Negeri 18 Tanah Abang has not used a computerized system, therefore the research conducted by the author aims to create an Academic Information System so that it can help and facilitate data processing.